Increased Frequency of Activated Switched Memory B Cells and Its Association With the Presence of Pulmonary Fibrosis in Diffuse Cutaneous Systemic Sclerosis Patients - Simon, Diána; Balogh, Péter; Erdő-Bonyár, Szabina; Böröcz, Katalin; Minier, Tünde; Czirják, László; Berki, Tímea (Frontiers in Immunology, 2021)
Disease-associated, high-affinity pathological autoantibody production is a well-described consequence of immune dysregulation affecting B cells in systemic sclerosis (SSc), including the distribution of B-cell subsets. We have previously shown that the increased relative frequency of CD19+CD27+IgD- switched memory B cells is associated with the severe form of SSc. This study sought to analyze memory B cell subsets using an extended range of markers for further subdivision based on CD19, IgD, CD27, CD38 and CD95 phenotype, to define relationship between the alterations of memory B cell subsets and the clinical features of SSc. Peripheral blood samples were obtained from 21 SSc patients, including 14 diffuse (dcSSc) and 7 limited (lcSSc) cutaneous SSc patients, with disease duration of 2.7 (±1.6) years. After purification of CD19+ B cells, multiparametric flow cytometry was performed and the frequencies of CD19+IgD-CD27-CD38+ double negative (DN) 1, CD19+IgDloCD27+CD38+ unswitched, CD19+IgD-CD27+CD38+CD95- resting switched and CD19+IgD-CD27+CD38-CD95+ activated switched memory (ASM) B cells were determined, and correlated with clinical features of SSc. The dcSSc patients had a higher frequency of ASM B cells (p=0.028) compared to lcSSc patients. The percentage of ASM B cells was elevated in anti-Scl-70 (anti-topoisomerase I) antibody positive patients compared to negative patients (p=0.016). Additionally, the frequency of ASM B cells was also increased in patients with pulmonary fibrosis (p=0.003) suggesting that patients with severe form of SSc have higher ASM B cell ratios. Furthermore, the ratio of DN B cells was decreased (p=0.029), while the level of anti-citrate synthase IgG natural autoantibody was elevated (p=0.028) in patients with active disease. Our observations on the increase of ASM B cells in dcSSc and in patients with pulmonary fibrosis may point to the association of this alteration with the severe form of the disease. Functionally the correlation of ASM B cells as effector memory-plasma cell with anti-topoisomerase I antibody positivity could reflect their contribution to pathological autoantibody production, whereas the decrease of memory precursor DN B cells and the increase of anti-citrate synthase IgG autoantibody may have potential significance in the assessment of disease activity.